STREET ART: SISI LAIN DARI FENOMENA MURAL JOGJA SEBUAH PERTARUNGAN IDENTITAS DAN KEPENTINGAN - Mr. Warsono (Ars: Jurnal Seni Rupa dan Desain, 2007)
Murals, as one o f the public art genres, has experienced rapid development in Jogjakarta, especiallysince the emergence o f Kclompok Ajwtik Komik as one o f its pioneers. Nevertheless, there are other factorsinfluencing the development o f murals, including socioculture, politics and economics, as well as globaldevelopment: lifestyle and the globalisation o f culture. The project o f Apotik Komik (Mural Kota, 2002)marked the beginning o f murals. As a result, murals spread sporadically throughout Jogja and even reachedremote corners o f the city. A new moniker is even attached to jogja as the City o f Murals.'The term "mural" (especially amongst the people o f Jogja) becomes a common word used to addressevery drawing and painting on most ivalls across the city. While, in fact, some works on walls in Jogjaoriginate from different genres. Several works are inclined towards the artistic style and possess roots whichare different front existing murals; some choose gruff ti and street art such as stencil, sticker, characters, etc.Differing from former mural artist communities, in the beginning o f2003 these groups began lo show theiractivities in Jogja s public spaces, and, o f course, they have different characteristics from existing murals.Keywords: street art, graffiti, public space